Four new species of Meligethes Stephens from China and additional data on other species of the genus (Coleoptera: Nitidulidae: Meligethinae) - Liu, Meike; Yang, Xingke; Huang, Min; Jelínek, Josef; Audisio, Paolo (Zootaxa, 2016)
Four new species of Meligethes Stephens, 1830, M. (s.str.) macrofemoratus (Shaanxi, Ningxia), M. (s.str.) yak (NW Sichuan), M. (s.str.) auropilosus (Tibet) and M. (Odontogethes) aurorugosus (Tibet) spp. nov., are described and illustrated from China. Diagnostic characters distinguishing these new species from closely related taxa are discussed. The previously unknown male of Meligethes (s.str.) aureolineatus Audisio, Sabatelli & Jelínek, 2015 from Sichuan and the previously unknown female of M. (Odontogethes) scrobescens Chen, Lin, Huang & Yang, 2015 from Sichuan are also described. Additional data are also presented on the geographic distribution and life history of other Chinese Meligethes species.
Keywords: brouci; China; velikost orgánu; Animal Distribution; Male; Organ Size; Ecosystem; anatomické struktury zvířat; mužské pohlaví; rozšíření zvířat; Animals; ženské pohlaví; Body Size; zvířata; Coleoptera; velikost těla; ekosystém; Čína; Female; Animal Structures